(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: Poetry is one of the sources from which scholars derive grammar and linguistic principles, but it is subject to weights that may detract from the increase in it and the decrease in it from the validity of the weight, and therefore it is permissible in it what is not permissible in speech, so the concept of committing poetic necessity: is the authorization of the poet to commit necessity in capacity, even if he is not forced The poet to it, and the views of the grammarians differed in committing the poetic necessity between those who permitted it and those who prevented it.